Physiological demands of water polo goalkeepers - Platanou, T.; Soultanakis, H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction The goalkeeper is the most important defense player and is very important in team sports. The outcome of team games depends on a great extend on his performance. While there is a number of studies that have dealt with the physiological demands of the other players in the water polo game, the information for the physiological demands of the goalkeepers is limited to two studies on kinematics analysis (Smith 1998, Platanou 2002) and in one study measuring lactic acid in the end of the periods (Rodriguez 1994). The purpose of this study was to examine the physiological demands of the goalkeepers during the game. We additionally investigated whether there were significant differences in the intensity of the game between the periods.